AJUSTAMENTO DE CONDUTA E JUSTIÇA ELEITORAL MULTIPORTAS: LIMITES E POSSIBILIDADES DE AUTOCOMPOSIÇÃO NO PROCESSO ELEITORAL - da Silva Sousa, Vicente de Paulo; Xerez Silva, André Garcia; Martins de Almeida, Frederico Rafael; Oliveira, Bruno de Sousa (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This article proposes an analysis of the possibilities of self-composition in the electoral process, based on reflections on improving the promotion of multi-door electoral justice, in light of art. 3, §§ 2 and 3, of the Code of Civil Procedure - Law No. 13.105/2015 and Resolution No. 125/2010, of the National Council of Justice, in the guise of art. 105-A, of Law No. 9.504/97. Based on a bibliographic review and a deductive approach to the topic of the adoption of self-composition techniques within the Electoral Justice, this study discusses the possibilities of concluding agreements in electoral matters, analyzing the adoption of self-composition techniques in specific themes, such as electoral propaganda in public spaces, electoral propaganda on the internet, radio and television, and in electoral actions that result in the declaration of ineligibility and revocation of registration or mandate. It is believed that this research could contribute to improving the use of self-composition methods in the Electoral Court, considering recent studies that support their effectiveness in resolving disputes, benefiting all stakeholders in the electoral process. The conclusion is that the discussion on the limits of self-composition in electoral matters is beneficial to ensure that the pursuit of greater cooperation and efficiency in the Electoral Court is based on adherence to democratic principles and the public interest.